Evaluation of the Quality of the iPresensi Berau Website Using Webqual and Importance Performance Analysis - Tunggal, Anggunan; Prastyo, Teguh; Ramadiani, Ramadiani (Jurnal Riset Ilmu Pendidikan, 2025)
The iPresensi Berau website is an online attendance system used by State Civil Apparatus (ASN) to record attendance in real time, while also supporting transparency and accountability in human resource management. This study aims to evaluate the quality of iPresensi Berau services from a user perspective by combining the WebQual 4.0 method—covering the dimensions of usability, information quality, and service interaction—and Importance–Performance Analysis (IPA). A descriptive quantitative approach was used through the distribution of a Google Form-based questionnaire to ASN in Berau Regency. Data analysis included calculating the level of conformity and mapping attributes in the IPA quadrant. The results showed that the average level of conformity between the level of importance and performance reached 98.90%, indicating that the website's performance has generally met user expectations. The IPA mapping identified three attributes in Quadrant I (top priority for improvement): (1) easy to understand site interactions, (2) easy to navigate, and (3) easy to understand information. Meanwhile, several attributes, such as clear website instructions, accurate information presentation, and secure and protected user data, fall into Quadrant II (maintained). These findings underscore the importance of improving interface aspects and information understandability, while maintaining the quality of already high-performing attributes.